Factores que afectan en la eficacia de la inseminación artificial en el programa de mejoramiento genético sostenible en bovinos de leche en las parroquias occidentales del cantón Latacunga. - Crespo Crespo, David Josue (2023)
Most of the producers that are part of the program of sustainable genetic improvement of dairy cattle in the province of Cotopaxi, use direct mating as a means of reproduction in their cows, however, this practice leads to worrying problems such as sexually transmitted diseases, such as bovine viral diarrhea, infectious bovine rhinotracheitis. The project was carried out to analyze the various factors that influence the success of artificial insemination (AI) in cows belonging to small farmers. The study was carried out in the western parishes of Latacunga canton, including Pastocalle, Toacaso, Guaytacama, Tanicuchi, Poaló, Eloy Alfaro and 11 de noviembre. A total of 595 animals were considered for the study, excluding those animals that had not reached reproductive maturity and did not have an updated health and deworming plan, thus counting a total of 32 inseminations in the period April - July 2023. The study followed a scientific and observational research approach. Environmental factors were evaluated, such as climate, temperature, humidity, altitude and soil characteristics, using applications such as "Thermometer - Hygrometer" and "Altimeter". In addition, animal factors were evaluated, such as body temperature, body condition, weight, age, nutrition, pathologies and number of calvings, using thermometers, bovinometric tapes and ultrasound scanners. For this purpose, data were collected and statistically analyzed in a contingency table using the Chi-square method. The results showed that climate is associated with AI. It was observed that in temperate climatic conditions, characterized by temperatures between 5°C and 10°C and the presence of natural shade, a significant increase in conception rate was achieved with a p-value of 0.003. In addition, a relationship was found between nutrition and AI, with a p-value of 0.003. A diet enriched with broccoli, due to its content of essential nutrients, had a positive impact on fertility and egg quality, which translated into an increase in conception rate after insemination. Also, an association between cow breed and AI was identified, with a p value of 0.03. It was observed that crossbred cows showed superior results in terms of conception after insemination. This higher efficiency is attributed to their favorable adaptation to the environment in which they live, which influences their reproductive capacity. No association was obtained between the factors involved in the AI technique. A protocol was established for the western parishes of Latacunga, it is advised to carry out the AI process with rigorous cleanliness and the convenience of carrying it out during temperate climates is highlighted, as well as improving the feeding of the cows and considering the adaptability of the breed to the surrounding environment.